ENHANCING CUSTOMER EXPERIENCE IN THE INDIAN TELECOM SECTOR - Upadhyay, Sanjay (Global journal of Business and Integral Security, 2023)
This research was conducted to derive the key factors responsible for influencing the enhanced customer experience in the Indian telecom sector and practical solutions that will help elevate the customer experience in the Indian telecom sector. This research validated the Indian mobile customers' preferences for factors that can improve their key telecom operator and also validated, through the same survey, the three practical solutions that will aid in elevating the customer experience, namely proactive customer care, local language customization, and special day delights. The study also suggests key improvements that Indian telecom operators should make in order to provide a comprehensive customer experience. In order to achieve this, the researcher conducted a survey of 1062 Indian mobile customers. The results of the analysis and verification of this research are summarized as follows. Based on the research’s findings, the Indian telecom sector must primarily focus on price, which is the key differentiator that impacts the customer experience. The outcome of this research also guides the telecom operators to cap price plan hikes and advises on the frequency of such hikes, which will trigger Indian mobile consumers to switch telecom operators. Based on the research’s findings, since none of the Indian telecom operators are already offering the three proposed solutions, it is highly recommended for them to start implementing one or all of the solutions if profitability and growth projections allow for the same. The three proposed solutions are proactive customer care, local language customization, and special-day delights. This research also acknowledges the challenges the Indian telecom operators may have in financing the three proposed solutions. To alleviate this concern, the research also validated that mobile consumers were willing to pay less than 5% of their monthly bill for such enhanced customer experiences. The research's key conclusions and suggestions will help create a practical framework for key enhancements that the Indian telecom sector must undertake to have an all-encompassing customer experience.